The Impact of Working Capital Management on Profitability in Micro and Small Processed Food Enterprises in Indonesia - Kamal, Syalma Nabila; Rachmina, Dwi; Feryanto, Feryanto (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
Effective management of working capital is essential for the profitability and long-term sustainability of micro and small-scale processed food businesses. However, at present, the business has not yet developed strong competency in managing working capital efficiently. This can certainly increase the potential for business bankruptcy, especially in the processed food business. This research examines the impact of working capital management, liquidity, and solvency ratios on the profitability of 1,563 micro and 241 small processed food enterprises in Indonesia. Multiple linear regression is used to assess the relationship between working capital management and profitability. The independent variables include the payable deferral period, inventory conversion period, current ratio, and debt-to-asset ratio, while profitability, as the dependent variable, is measured by return on assets (ROA). The findings indicate that both the payable deferral period and debt-to-asset ratio significantly affect the profitability of micro and small businesses, with the current ratio having a particular effect on the profitability of small businesses. These findings suggest that improving financial management practices, such as daily sales optimization and enhanced cash flow monitoring, could significantly enhance profitability in the micro and small processed food sector.